Personality Traits and Family Context in Prisoners, Members of the Prison Security Officers, and the General Population - Vučićević, Marija; Međedović, Janko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The aim of this research is to investigate the differences between members of the prison security service, convicts, and the control group, in the degree of expression of basic personality traits, Dark Tetrad traits, as well as differences in family context variables (family dysfunctions, childhood poverty, and the number of siblings). The sample consisted of three groups of 100 respondents each: sentenced prisoners, prison security officers, and the general population with no history of criminal behavior. We administered the following inventories: Dirty Dozen for Dark Triad traits, Core Sadism Scale – VAST, Mini-IPIP6 for general personality traits, as well as a scale of adverse environment in childhood. We expected that the Dark Tetrad traits, unfavorable environment and the number of siblings would be the highest in the convicts group; furthermore, this group should have the lowest levels of Agreeableness, Conscientiousness, and Honesty traits. Most of the hypotheses raised have not been confirmed; however, those which were congruent with the data were mostly related to the family context. Discriminatory analysis showed that the general population was characterized by lower Conscientiousness and lower sibling numbers than convicted persons. This analysis further showed that members of the security service are distinguished by better family relationships and higher levels of the Honesty trait than convicted persons. Deviations from the hypotheses can largely be the product of methodological limitations of the research – the instruments used and insufficient control in the data collection process.